Analisis Faktor Penyebab Kurangnya Minat Remaja Terhadap Pendidikan Perguruan Tinggi - Irwan Abdullah; Muhammad Ichsan A. Gani (Cetta: Jurnal Ilmu Pendidikan, 2022)
This research is expected to find out: 1) the inhibiting variables that cause the lack of attention of the youth of Jambula Village to study in additional schools. 2) financial/economic elements that make the younger generation of Jambula Village ignore further teaching. This kind of investigation is an undeniable abstract judgment. The number of respondents was 15. The certainty of the method in this study used purposive review/sampling, with the younger generation in Jambula Village as the main witnesses and the mentors/caregivers of teenagers as resource persons. Data collection techniques used are deepening/perception, meetings and documentation. The data checking methodology uses data reduction, data display and conclusion drawing. The results of this study indicate that: 1) the internal components that make the youth of Jambula City further foster youth are: a) lack of inspiration or desire to continue to college, b) wanting to be independent by looking for work after continuing high school. 2) External factors that cause it are the financial or economic limitations of the school are very large and the social environment factor itself.